Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1103/physrevb.87.060104
|View full text |Cite
|
Sign up to set email alerts
|

Electrodynamic response and stability of molecular crystals

Abstract: We show that electrodynamic dipolar interactions, responsible for long-range fluctuations in matter, play a significant role in the stability of molecular crystals. Density functional theory calculations with van der Waals interactions determined from a semilocal "atom-in-a-molecule" model result in a large overestimation of the dielectric constants and sublimation enthalpies for polyacene crystals from naphthalene to pentacene, whereas an accurate treatment of nonlocal electrodynamic response leads to an agre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 40 publications
(95 reference statements)
1
46
0
Order By: Relevance
“…34,72 The importance of including manybody effects goes beyond cohesive energies; it has been recently shown that the prediction of the dielectric constants of the polyacene crystals is also significantly improved by the MBD method. 63 …”
Section: Comparison With (Effective) Pairwise Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…34,72 The importance of including manybody effects goes beyond cohesive energies; it has been recently shown that the prediction of the dielectric constants of the polyacene crystals is also significantly improved by the MBD method. 63 …”
Section: Comparison With (Effective) Pairwise Treatmentsmentioning
confidence: 99%
“…63 To study the broad importance of phonon dispersion on the vibrational contributions unit-cell and supercell (of at least 9-10 Å length in each direction) calculations have been performed for the whole database of molecular crystals. The resulting vibrational contributions at 298 K are shown in Figure 2.…”
Section: A Vibrational Contributions To Theoretical Lattice Energiesmentioning
confidence: 99%
“…Therefore, the observed changes in the optical spectrum upon crystallization of polyacenes are accompanied by a change in the molecular polarizability. These changes in polarization will also directly impact the crystal lattice energy [52].…”
Section: A Soft Organic Materialsmentioning
confidence: 99%
“…In recent years, substantial progress has been achieved in the theoretical prediction of structures and stabilities of molecular crystals by using vdW-inclusive DFA approaches [43,44]. Today, the structures of (simple) organic molecular crystals can be predicted with an accuracy of 2-3% [45][46][47] and cohesive energies to 1-2 kcal/mol [43][44][45]48].…”
Section: A Soft Organic Materialsmentioning
confidence: 99%
“…More recently, the vibrational modes of gas-phase naphthalenein particular, infrared and Raman active modes-as well as the zone-center modes of crystalline naphthalene have also been reproduced successfully with ab initio methods 53,59,[64][65][66][67][68] , although the mode assignments depend somewhat on the level of theory and functional 53,68 . Finally, Schatschneider et al 69 and Reilly and Tkatchenko 70 used vdW-corrected DFT to obtain the zero-point energy and vibrational contribution (integrated over the Brillouin zone) to the lattice energy of several acenes, respectively, using the TkatchenkoScheffler pairwise approach; however, these studies did not provide any details of the phonon spectrum.…”
Section: Introductionmentioning
confidence: 99%